2011
DOI: 10.1007/s00464-011-1999-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full-thickness plication versus laparoscopic fundoplication: a prospective study on quality of life and symptom control

Abstract: Endoscopic plication and laparoscopic fundoplication resulted in significant symptom improvement with similar quality-of-life scores in a selected patient population with GERD, whereas operative treatment was more effective in the relief of heartburn and regurgitation at the expense of higher short-term dysphagia rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…If necessary for a tight closure of the restructured gastroesophageal junction, 1 or 2 additional sutures were placed in the same manner, as described previously, until a tight closure around a 5.8-mm video endoscope was achieved. 10,13 In this protocol, additional treatment with another suture was permitted and performed in the same manner in case of inadequate response to therapy.…”
Section: Endoscopic Plication Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…If necessary for a tight closure of the restructured gastroesophageal junction, 1 or 2 additional sutures were placed in the same manner, as described previously, until a tight closure around a 5.8-mm video endoscope was achieved. 10,13 In this protocol, additional treatment with another suture was permitted and performed in the same manner in case of inadequate response to therapy.…”
Section: Endoscopic Plication Techniquementioning
confidence: 99%
“…13 In particular, the symptoms of heartburn, regurgitation, chest pain, cough, hoarseness, asthma, dysphagia, fullness, diarrhea, flatulence, constipation, belching, bloating, and distortion of taste were graded as none (0), once per week (1), several times per week (2), daily (3), and constantly (4). The intensity of the above symptoms was graded as none (0), mild (1), moderate (2), severe (3), and extremely severe (4).…”
Section: Symptom and Side Effect Evaluationmentioning
confidence: 99%
“…Both methods were reflected by similar degree of improvement in the HRQOL scores prior to the treatment and 3 and 12 months thereafter. More pronounced reduction in the incidence of heartburn and regurgitation was observed in the surgically treated group, along with an increase in the incidence of dysphagia [54]. Recently, the same authors confirmed that both procedures are associated with similar improvements of general subjective outcome parameters and that laparoscopic anti-reflux fundoplication provides more effective control of reflux-related symptoms.…”
Section: Comparison Of Quality Of Life In Patients Treated Endoscopicmentioning
confidence: 82%
“…Recently published meta-analysis, including 1441 patients treated with the Stretta method revealed that this procedure results in a marked attenuation of reflux symptoms and improvement of HRQOL, and may constitute an alternative to pharmacotherapy and surgical treatment in a selected group of patients [52]. Currently, endoscopic full-thickness plication seems to be a very promising treatment option due to its documented long-term efficacy in reflux symptoms control in the majority of patients, improvement in the quality of life, and lack of side effects seen after laparoscopic fundoplication [53,54].…”
Section: The Influence Of Endoscopic Treatment Of Gerd On Quality Of mentioning
confidence: 99%
“…Another study [38] compares the efficacy of endoscopic application and laparoscopic fundoplication on quality of life and the control of symptoms. 60 patients with documented reflux disease were randomly assigned to endoscopic or laparoscopic endoscopy.…”
Section: Muse (Medigus Ultrasonicmentioning
confidence: 99%